Respiratory Syncytial Virus Genotypes, Host Immune Profiles, and Disease Severity in Young Children Hospitalized With Bronchiolitis. (17th October 2017) - Rodriguez-Fernandez, Rosa; Tapia, Lorena I; Yang, Chin-Fen; Torres, Juan Pablo; Chavez-Bueno, Susana; Garcia, Carla; Jaramillo, Lisa M; Moore-Clingenpeel, Melissa; Jafri, Hasan S; Peeples, Mark E; Piedra, Pedro A; Ramilo, Octavio; et al.
Abstract : Infants hospitalized with RSV A/GA5 bronchiolitis showed greater clinical severity, decreased interferon expression, and enhanced overexpression of neutrophil-related genes, compared with the GA2 or BA genotypes, suggesting the possibility that RSV strain-specific differences may contribute to clinical severity. Abstract: Background: Data on how respiratory syncytial virus (RSV) genotypes influence disease severity and host immune responses is limited. Here, we characterized the genetic variability of RSV during 5 seasons, and evaluated the role of RSV subtypes, genotypes, and viral loads in disease severity and host transcriptional profiles. Methods: A prospective, observational study was carried out, including a convenience sample of healthy infants hospitalized with RSV bronchiolitis. Nasopharyngeal samples for viral load quantitation, typing, and genotyping, and blood samples for transcriptome analyses were obtained within 24 hours of hospitalization. Multivariate models were constructed to identify virologic and clinical variables predictive of clinical outcomes. Results: We enrolled 253 infants (median age 2.1 [25%–75% interquartile range] months). RSV A infections predominated over RSV B and showed greater genotype variability. RSV A/GA2, A/GA5, and RSV B/BA were the most common genotypes identified. Compared to GA2 or BA, infants with GA5 infections had higher viral loads. GA5 infections were associated with longer hospital stay, and with less activation of interferon and increased overexpression of neutrophil genes. Conclusions: RSV A infections were more frequent than RSV B, and displayed greater variability. GA5 infections were associated with enhanced disease severity and distinct host immune responses.